Gender Inequality in The Novel “Death of an Ex-Minister” by Nawal El Saadawi - Juhana Juhana; Nur Qalbi; Sri Arfani (Makassar State University, 2021)
Abstract. This study aims to describe the gender inequality contained in the novel Death of an Ex-Minister by Nawal el Saadawi using gender theory by Mansour Fakih (2005) which includes marginalization, subordination, stereotype, violence, and workload. The method used was descriptive qualitative. The results showed that there was gender inequality that was manifested in four forms: marginalization, subordination, stereotyping, and violence. Marginalization occurs in the form of dismissals by male superiors to female employees who were considered to often express opinions that differ from them. Subordination was indicated by the position of women who were lower than men. Whereas, stereotyping occurred with the negative attachment of a husband to his wife that because he was the one who gave food he had the right to do anything to his wife. The violence occurred in the form of physical violence by a husband against his wife and sexual violence experienced by a woman who was raped by ten men. Keywords: Gender, Gender Inequality, the novel Death of an Ex-Minister